Intervenções cirúrgicas para o tratamento do deslocamento anterior do disco da articulação temporomandibular (ATM): Revisão de literatura - Gomes, Lucas de Souza (2023)
The temporomandibular joint (TMJ) is one of the most complex joints in the human body and can be affected by dysfunctions (TMD) between the muscles, ligaments and attached structures, which, if in unphysiological conditions, can cause the patient intense pain and functional impairment. For the diagnosis of joint dysfunctions, data collected during anamnesis, intra and extra-oral physical examination and imaging tests are used to guide the treatment required for each patient. Anterior articular disk displacement is an internal derangement that, when associated with painful symptoms and impact on the functionality of the stomatognathic system, requires intervention. Initially, interventions can be performed through conservative treatments, and only when these fail to demonstrate effective analgesic results and full functional reestablishment should one opt for surgical interventions. The purpose of this paper is to report the main surgical approaches described in the literature for the treatment of anterior displacement of the TMJ disk and their main clinical implications.